Effects of Position of Rainfed Rice Field in a Toposequence on Water Availability and Rice Yield in Central Java, Indonesia - HUSEIN SUGANDA; E.P PANINGBATAN; L.C GUERRA; T.P TUONG (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2003)
The productivity of rainfed rice needs to be increased in order to support the Indonesian Food Security programs, especially rice. Rainfall is one of the main sources of the water availability on the rainfed rice field. This research was conducted from October 2000 to February 2001 at four sites in Central Java Province. The objectives of this research were to study thevariability of water availability that influenced by toposequen’s position and to analyze the rice yields due to treatments on toposequence. This experiment was carried out in the farmers’ field using “Group Balanced Block in Split-Split Plot Design” and Inceptisols soil order. Mainplots were the four positions in toposequence (top, upper middle, lower middle, and bottom), and the four villages were used as replication. The sub-plot wastreatments group and sub-sub-plot consists of group-1: farmer’s practice and without weeding; group-2: farmer’s practice without fertilizer and added recommended fertilizer. The research showed that rainfall affected the fluctuation of ground water table and standing water periods. The straw and unhulled rice/grain yields at the bottom position was the highest, and was significantly different from the top position of the toposequence, namely 7.1 and 5.6 t ha-1 for straw yield while 5.2 and 4.0 t ha-1 for grainyield. Without weeding, the straw and grain yields decreased by 1.0 t ha-1 (6.1 to 5.1 t ha-1) and 0.8 t ha-1 (4.6 to 3.8 t ha-1). While, without fertilization, the straw and grain yields were produced only 4.4 and 3.8 t ha-1. Straw and grain yields increased up to 7.0 and 5.1 t ha-1, respectively, when recommended fertilizers were applied.